High-energy interactions at the Pierre Auger Observatory - Conceição, Ruben (2015)
The interaction of Ultra High Energy Cosmic Rays (UHECRs) with the atoms of the atmosphere can occur at center-of-mass energies that surpass 100 TeV, while present human-made accelerators go up to 13 TeV. Therefore it provides a unique opportunity to explore hadronic interactions at the highest energies. However, the extraction of hadronic interaction properties from the Extensive Air Showers (EAS) characteristics, which are induced by the UHECR, is intrinsically related to the nature of the primary cosmic ray. As such, to break the degeneracy between hadronic interactions and primary mass composition, a consistent description of the shower observables must be achieved. Such detailed studies have been conducted in the last years at the Pierre Auger Observatory, the largest UHECRs detector in the world. It combines two complementary techniques to measure the EAS characteristics. In this talk, we will present the latest measurements on shower observables, both on the electromagnetic and muonic shower components, and its interpretation in terms of the primary mass composition. Its impact regarding particle physics will be discussed, in particular the measurement of the proton-air cross section. Finally, through the joint analysis of the different measurements, it will be shown that none of the post-LHC high-energy hadronic interaction models can satisfactorily describe the data.